Plasma microRNA profiles: identification of miR-1229-3p as a novel chemoresistant and prognostic biomarker in gastric cancer - Nishibeppu, Keiji (Sci Rep, 2020)
This study aimed to explore novel microRNAs in plasma for predicting chemoresistance in adjuvant chemotherapy for patients with gastric cancer (GC). We used the Toray 3D-Gene microRNA array-based approach to compare preoperative plasma microRNA levels between GC patients with and without recurrences after curative gastrectomy. All patients underwent adjuvant chemotherapy with S-1, an oral fluoropyrimidine. Of 2566 candidates, six candidate microRNAs (miR-1229-3p, 1249-5p, 762, 711, 1268a and 1260b), which were highly expressed in the preoperative plasma of patients with subsequent recurrences, were selected. In a large-scale validation analysis by quantitative RT-PCR, we focused on high plasma levels of miR-1229-3p, which was an independent poor prognostic factor for recurrence free survival (P = 0.009, HR = 3.71). Overexpression of miR-1229-3p in GC cells induced significant chemoresistance to 5-fluorouracil (5-FU), up-regulation of thymidylate synthase (TS) and dihydroprimidine dehydrogenase (DPD) and down-regulation of SLC22A7 both in vitro and in vivo. Intraperitoneal injection of miR-1229-3p in mice induced significant chemoresistance to 5-FU, accompanied by high levels of miR-1229-3p in plasma and tumor tissue. These findings suggest that plasma miR-1229-3p might be a clinically useful biomarker for predicting chemoresistance to S-1 and selecting other or combined intensive chemotherapy regimens in GC patients.